Let's start with the given equation:
\[ 20 - 2p = 6 + 5p \]
Now, as suggested, we will add \(2p\) to both sides of the equation.
Doing this gives us:
\[ 20 - 2p + 2p = 6 + 5p + 2p \]
This simplifies to:
\[ 20 = 6 + 7p \]
Now we have moved all the \(p\) terms to the right side of the equation. Next, we can rewrite the equation:
\[ 20 = 6 + 7p \]
So, we can now see that all terms involving \(p\) are on the right side of the equation. The remaining values are \(20\) on the left and \(6\) on the right, along with the \(7p\) term.
To find the value of \(p\), we can continue solving the equation:
- Subtract \(6\) from both sides:
\[ 20 - 6 = 7p \]
This simplifies to:
\[ 14 = 7p \]
- Now, divide both sides by \(7\):
\[ p = \frac{14}{7} \]
This gives us:
\[ p = 2 \]
Therefore, the value of \(p\) is \(2\).